The application of noise maps for traffic noise reduction - Avsar, Yasar; Gumus, Beyza D. (INST NOISE CONTROL ENGINEERING, 2011)
Using a computer model, a traffic noise map was prepared for a 1-km section of one of the most frequently travelled roads in Istanbul. Calculations were carried out in grid intervals of 10 m at 4 m above ground level. Field measurements were also conducted for the same region. The traffic noise map and noise level measurements are compared. Predictions of noise reduction for decreasing vehicle speed, the number of heavy vehicles and adding noise barriers are presented. (C) 2011 Institute of Noise Control Engineering.
Keywords: VEGETATION; ROAD; Acoustics; Engineering